METHODS OF STUDYING GROUP I ELEMENTS USING INTERACTIVE METHODS - Jumabaev, Berdakh Aytbaevich; Sherimmatova, Sarvinoz Rasulovna; Sherimmatova, Mahfuza Rasulovna (SCIENCE and SOCIETY, 2026)
This article highlights effective ways of teaching Group I elements of inorganic chemistry based on interactive methods. It is noted that the interactive approach serves to increase the activity of students, strengthen their participation in the process, and develop independent thinking and analytical skills.